Aplicação do monitoramento terapêutico, genotipagem e estudo de farmacocinética populacional em pacientes tratados com voriconazol - Petreceli, Rodrigo Redel (2024)
Voriconazole (VCZ) is a triazole antifungal used for the treatment and prophylaxis of invasive fungal infections. It exhibits nonlinear pharmacokinetics and has a narrow therapeutic range. Therefore, therapeutic drug monitoring (TDM) has been recommended to optimize clinical outcomes. Population pharmacokinetic (popPK) modeling allows the identification of population-specific characteristics and provides data for evaluating alternative dosing regimens through simulations. The aim of this study was to conduct a TDM study of VCZ in patients treated at the University Hospital of Santa Maria, assess CYP2C19 genotyping, and develop a popPK model to evaluate alternative dosing regimens. To this end, blood samples were collected at peak and trough times and analyzed by high-performance liquid chromatography coupled with a photodiode array detector (HPLC-DAD). Genotyping of clinically relevant CYP2C19 polymorphisms (*2, *3, and *17) was performed using real-time polymerase chain reaction (qPCR), and the corresponding phenotype was estimated from the genotype. PopPK modeling and pharmacokinetic/pharmacodynamic (PK/PD) analysis were performed using the NONMEM software (v.7.4.0), and statistical analysis was conducted in R (v.4.4.1). A total of 124 samples from 51 patients aged 2 to 71 years were included. The main diagnoses were acute lymphoid and myeloid leukemia. Median VCZ trough plasma concentrations (Ctrough) were 1.08 (IQR 0.46–2.56) and 1.84 (IQR 0.60–3.57) mg/L for pediatric and adult patients, respectively. Ctrough was correlated with peak concentrations (Cpeak), dose, and daily dose (r = 0.82, 0.47, and 0.46, respectively, p < 0.01). High proportions of Ctrough outside the therapeutic range were observed, with 42.3% and 33.3% subtherapeutic concentrations for adult and pediatric patients, respectively. Observed frequencies for CYP2C19 phenotypes were 28.2% intermediate metabolizers (IM), 56.4% normal metabolizers (NM), and 15.4% rapid or ultra-rapid metabolizers (RM/UM). Adult RM/UM patients showed higher proportions of subtherapeutic concentrations, while pediatric IM patients exhibited more subtherapeutic levels. The popPK model that best described the population was a one-compartment model with linear absorption and nonlinear elimination. A mixture model for maximum elimination rate (Vmax) was used to estimate CYP2C19 metabolizer subpopulations, generating three groups with Vmax values of 32.33 mg/h, 45.89 mg/h, and 93.56 mg/h, corresponding to 33.2%, 41.1%, and 25.7% of the population, respectively. Doses of 6 and 12 mg/kg intravenously (IV) every 12 hours (BID) and 400 mg orally (PO) BID were required to achieve a probability of target attainment (PTA) >90%, depending on the subpopulation. High variability in Ctrough and high percentages of subtherapeutic concentrations were observed. The distribution of CYP2C19 phenotypes was consistent with expectations for the population. The popPK model described the population well and was useful for estimating metabolizer groups comparable to CYP2C19 phenotypes. The doses used were insufficient to achieve PK/PD targets, and higher doses may be necessary for pediatric patients and rapid metabolizers.